A Comprehensive Study on Marine Sample Collection Techniques for Xanthone Screening - Krishnamurthy, Vishwakarma Ravindrakumar; Kirthiga, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study focuses on the collection of marine samples and the subsequent screening of xanthone compounds from the marine fungi Aspergillus sydowii. Marine fungi, especially those from the genus Aspergillus, are known for producing a wide array of bioactive compounds with significant therapeutic potential. The primary objective was to isolate and identify fungal strains capable of producing xanthones and evaluate their bioactive properties. Samples were collected from various marine environments, including coastal waters and deep-sea sediments, and preserved under sterile conditions. Fungal isolates were cultured, and xanthones were extracted and purified using chromatographic techniques. The purified compounds were identified using spectroscopic methods and tested for their antimicrobial and antioxidant activities. The results revealed that the xanthones exhibited potent antimicrobial activity against Staphylococcus aureus, Escherichia coli, and Candida albicans, as well as strong antioxidant properties. These findings highlight the potential of marine-derived xanthones for pharmaceutical applications, including the development of new antibiotics and antioxidant therapies. The study underscores the importance of marine fungi in the discovery of novel bioactive compounds and their potential applications in biotechnology and industry.